Evaluate the level of pain intensity in children after thoracic surgical interventions - Tomaszek, Lucyna (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Regular evaluation of pain intensity with age-specific measuring scales, which correspond to the perception skills of children, comprises the basis for effective pain relief after surgical interventions. Purpose. The purpose of this work was to evaluate the level of pain intensity in children during the first 24 hours after thoracic surgical interventions and analyze the following research issues: 1. To what extent chosen pain-relief method, kind of surgical intervention, and patient’s gender affected pain intensity? 2. Which measuring scale for pain intensity (numerical or verbal) turned out to be more useful in postoperative pain evaluation? 3. What was the correlation between physilological parameters (blood pressure, pulse rate) and subjective pain experience in the studied groups? Material and methods. The study was performed in two groups of children aged from 7 to 18 years. Respondents from group I (n = 30) received after surgery continuous intravenous infusion of morphine. Group II (n = 59) comprised patients with thoracic extradural catheter and received 0.25% bupivacaine or 0,25% bupivacaine with morphine. Pain intensity was evaluated five times in both numerical and verbal scales. Results and conclusions. The intensity of postoperative pain depends on the method of applied analgesia. No relation between pain intensity and kind of thoracic surgical intervention or patient’s gender was found. Both scales measuring pain intensity (numerical and verbal) turned out to be useful as far as postoperative pain evaluation was concerned. Numerical scale should be the first chioce for it allows greated differentiation of pain intensity. Physilological parameters showed poor correlation with subjective pain assessment. Therefore, they should be treated only as additional measuring tools.